Agri-Business Opportunities through Innovative Technologies, Prospects and the Way Forward - Mysore, Sudha; Kalkal, Amit; Singh, Madan Mohan Sharan; Gopal, Krishan (Indian Farming, 2020)
Innovative technical knowledge, often termed as ‘improved technology’ plays an important role in yield and income enhancement in agriculture and allied sectors. Research institutions, especially the publicly funded ones, often tend to be the primary sources of such technical knowledge in the form of improved varieties, hybrids and other technology-based products. Dissemination of the same for large scale adoption by the end users has often been a limiting factor, given the inadequate infrastructure and/or resources at the disposal of these research and development-based institutions. Hence, as a means of spearheading large-scale dissemination of these innovative processes and products, a novel system of ‘developing and nurturing technology-based businesses’ has been gaining momentum world over, which also formed a part of the UNs millennial sustainable development agenda.